Reference values for intracoronary doppler flow velocity-derived hyperaemic microvascular resistance index. (14th October 2021) - Feenstra, R G T; Seitz, A; Boerhout, C K M; De Winter, R J; Ong, P; Beijk, M A M; Piek, J J; Sechtem, U; Van De Hoef, T P
Abstract: Background: Invasive assessments of microvascular function are rapidly becoming an integral part of physiological assessment in chronic coronary syndromes. Objective: We aimed to establish a reference range for Doppler flow velocity-derived hyperaemic microvascular resistance index in a cohort of ANOCA patients with no structural pathophysiological alterations in the coronary circulation. Methods: The reference population consisted of ANOCA patients undergoing invasive coronary vasomotor function assessment who had a coronary flow reserve (CFR) >2.5, and had either (1) tested negatively for spasm provocation (n=12) or (2) tested positively with only angina at rest (n=29). A reference range for HMR was established using a non-parametric method and correlations with clinical characteristics were determined using a spearman rank correlation analysis. Results: In 41 patients median HMR amounted to 1.6 mmHg/cm/s [Q1, Q3: 1.3, 2.2 mmHg/cm/s]. The reference range for HMR that is applicable to 95% of the population was 0.8 mmHg/cm/s (90% CI: 0.8–1.0 mmHg/cm/s) to 2.7 mmHg/cm/s (90% CI: 2.6–2.7 mmHg/cm/s). No significant correlations were found between HMR and clinical characteristics. Conclusion: In this reference population undergoing invasive coronary vasomotor function testing, the 90% confidence interval of the HMR upper limit of normal ranges from 2.6 to 2.7 mmHg/cm/s. A >2.5 mmHg/cm/s HMR threshold can be used to identify abnormal microvascular resistance in daily clinical practice. Funding Acknowledgement: Type of funding sources: None.